TaqMan qPCR quantification of the Cytb gene for precise determination of camel milk in dairy products - Qin Na; Rendalai Si; Liang Ming; Li Yi; Jing He; Tuyatsetseg Jambal; Rimutu Ji (PLoS ONE, 2026)
Camel milk often faces quality control problems because it is vulnerable to adulteration with inferior dairy sources or plant-derived additives. Many existing DNA-based detection methods rely on suitable endogenous reference genes. This study aimed to develop an absolute quantification strategy based on real-time quantitative polymerase chain reaction using TaqMan probes. A recombinant plasmid standard containing camel-specific cytochrome b ( Cytb ) genes was designed. The resulting standard curve revealed high linearity ( R ² = 0.9982) across six orders of magnitude, enabling precise quantification of copy numbers. The primers and probes demonstrated high specificity for camel DNA, and the plasmid standards met quality criteria (A260/280 = 1.82; concentration deviation <2%). The method achieved a sensitivity of 6.39 × 10² copies/μL. For samples containing 5%–100% of camel milk, the coefficient of variation ranged from 0.99% to 5.20%, and the recovery rates for spiked products ranged from 97.5% to 107.5%. By providing absolute quantification without requiring a reference gene, this method offers a robust solution for detecting camel milk adulteration in dairy products.